A Mitochondria‐Targeted Photosensitizer Showing Improved Photodynamic Therapy Effects Under Hypoxia. (6th July 2016) - Lv, Wen; Zhang, Zhang; Zhang, Kenneth Yin; Yang, Huiran; Liu, Shujuan; Xu, Aqiang; Guo, Song; Zhao, Qiang; Huang, Wei
Abstract: Organelle‐targeted photosensitizers have been reported to be effective photodynamic therapy (PDT) agents. In this work, we designed and synthesized two iridium(III) complexes that specifically stain the mitochondria and lysosomes of living cells, respectively. Both complexes exhibited long‐lived phosphorescence, which is sensitive to oxygen quenching. The photocytotoxicity of the complexes was evaluated under normoxic and hypoxic conditions. The results showed that HeLa cells treated with the mitochondria‐targeted complex maintained a slower respiration rate, leading to a higher intracellular oxygen level under hypoxia. As a result, this complex exhibited an improved PDT effect compared to the lysosome‐targeted complex, especially under hypoxia conditions, suggestive of a higher practicable potential of mitochondria‐targeted PDT agents in cancer therapy.